Inflammatory Gene Expression of Human Perivascular Adipose Tissue in Abdominal Aortic Aneurysms. (June 2021) - Meekel, Jorn P.; Dias-Neto, Marina; Bogunovic, Natalija; Conceição, Gloria; Sousa-Mendes, Claudia; Stoll, Gawin R.; Leite-Moreira, Adelino; Huynh, Jennifer; Micha, Dimitra; Eringa, Etto C.; Balm, Ron; Blankensteijn, Jan D.; et al.
Abstract : Objective: Perivascular adipose tissue (PVAT) contributes to vascular homeostasis and is increasingly linked to vascular pathology. PVAT density and volume were associated with abdominal aortic aneurysm (AAA) presence and dimensions on imaging. However, mechanisms underlying the role of PVAT in AAA have not been clarified. This study aimed to explore differences in PVAT from AAA using gene expression and functional tests. Methods: Human aortic PVAT and control subcutaneous adipose tissue were collected during open AAA surgery. Gene analyses and functional tests were performed. The control group consisted of healthy aorta from non-living renal transplant donors. Gene expression tests were performed to study genes potentially involved in various inflammatory processes and AAA related genes. Live PVAT and subcutaneous adipose tissue (SAT) from AAA were used for ex vivo co-culture with smooth muscle cells (SMCs) retrieved from non-pathological aortas. Results: Adipose tissue was harvested from 27 AAA patients ( n [gene expression] = 22, n [functional tests] = 5) and five control patients. An increased inflammatory gene expression of PTPRC ( p  = .008), CXCL8 ( p  = .033), LCK ( p  = .003), CCL5 ( p  = .004) and an increase in extracellular matrix breakdown marker MMP9 ( p  = .016) were found in AAA compared with controls. Also, there was a decreased anti-inflammatory gene expression of PPARG in AAA compared with controls ( p  = .040). SMC co-cultures from non-pathological aortas with PVAT from AAA showed increased MMP9 ( p  = .033) and SMTN ( p  = .008) expression and SAT increased SMTN expression in these SMC. Conclusion: The data revealed that PVAT from AAA shows an increased pro-inflammatory and matrix metallopeptidase gene expression and decreased anti-inflammatory gene expression. Furthermore, increased expression of genes involved in aneurysm formation was found in healthy SMC co-culture with PVAT of AAA patients. Therefore, PVAT from AAA might contribute to inflammation of the adjacent aortic wall and thereby plays a possible role in AAA pathophysiology. These proposed pathways of inflammatory induction could reveal new therapeutic targets in AAA treatment.